Discovering Islam: Making Sense of Muslim History and Society by Akbar S. Ahmed. New York: Routledge and Kegan Paul, Ltd., 1988. pp. 251 (American Journal of Islam and Society, 1988)
This book, written by Akbar Ahmed, is particularly apt and to the point.The book’s title and subtitle seem, to this reviewer at least, an accurate reflectionof its content: it has an introduction also called “Discovering Islam”, thentwo major sections (each divided into chapters of unequal length; the firstand longer on ”The Pattern of Muslim History” and the second on”Contempomy Muslim Society” (with a conclusion again entitled “DiscoveringIslam”). As Ahmed states at the outset, he writes as a committed participantin, as well as an observer of, Islam, and furthermore, he makes no bonesabout his “South Asian” (read ”Pakistani“) perspective and bias with respectto Islam as a whole.Ahmed has already observed in some of his earlier work, that there isonly one Islam, not many “islams” (contrary to the views asserted recentlyby a number of non-Muslim students of the subject); and this is so despitethe wide range and disparity of Muslim societies around the globe. Neitherof these arguments is original with its present proponents. Ahmed puts forwardboth his view of the Islamic ideal, as well as the way some Muslims ordertheir lives with respect to this ideal, with surprising force and vigor.He states, “Economic, political and ethnic-social, cultural pressures actto compromise notions of the ideal, thereby creating ambiguity around it.The demarcation of Muslim societies is therefore not division between whiteideal and black non-ideal, but an ongoing relationship between the two markedby areas of grey. Taken together the arguments will assist us in our searchfor . . . an Islamic world-view of society and history” (p. 5). A further verytelling quote which reveals the book to be neither an apology for, nor anattack on, the West (of which its author is admittedly and justifiably critical),but a clear statement: ”While the twentieth century cannot reject Islam-itis here to stay as a force; in turn, Islam must accept the twentieth century.It will not go away, and rejection is the easy way out. Islam must come toterms with the twentieth century; by doing so it will come to terms withitself‘ (p. 8).In the first section of the book we are taken on a tour of Islamic history.It is of necessity selective, but both the wide-angle lens shots, as well as ...